PENERAPAN BLENDED LEARNING BERBASIS SCHOOLOGY UNTUK MENINGKATKAN HASIL BELAJAR ADMINISTRASI HUMAS DAN KEPROTOKOLAN DI SMK NEGERI 1 SURAKARTA - Efi Nur Fidiatun; C. Dyah Sulistyaningrum I; Patni Ninghardjanti (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2018)
The purpose of this study is to determine the improvement of learning outcomes of students class XII AP 3 subjects of public relations administration and protocol in SMK Negeri 1 Surakarta through the application of learning models based bladed learning applications schoology. The type of research conducted by researchers is Classroom Action Research (CAR). Before applied learning model of bladed learning application based on schoology grade average grade in cognitive domain 66,84 percentage of 29,03% completeness, affective domain of 64,52% mastery percentage with mean value that is B, psychomotor realm is 69 , 81 with a percentage of completeness of 48.39%. In the first cycle of learning outcomes of learners is the average class in the cognitive domain of 80.26 with the percentage mastery 87.10%, affective domain percentage mask 90.32% with the average value of B, the average psychomotor realm is 79, 68 with the percentage masked 80.65%. In the second cycle of learning outcomes of learners is the average class in the cognitive domain of 85.29 or with 100% completeness percentage, affective domain percentage mastery 100% average value of B, the average psychomotor realm is 85.03 percentage of 100 %.